Economic Development / Problems, Principles, and Policies - Higgins Benjamin (W.W. Norton & Company, 1968)
Preface, Introduction: The Prolem, General Theories, Lessons of History, Theories of Underdevelopment, Policies, Case Studies, Afterword.